Pengaruh Partisipasi Anggaran dan Kejelasan Sasaran Anggaran Terhadap Kinerja Manajerial Pada Kantor Gabungan Dinas Kota Makassar - Fatihah; Radja, Muh. Jusuf; Anwar (Insan Cita Bongaya Research Journal, 2023)
This study aims to test and analyze the effect of budget participation and clarity of budget targets on managerial performance at the Makassar City Office Joint Office. The approach used is a descriptive approach with quantitative methods. The population is the head of the agency/skpd, the head of the section/field, and the head of the subdivision at the Joint Office of the Makssar City Office, while the sample taken amounted to 48 respondents. The sampling method is Nonprobability Sampling. Hypothesis testing using multiple linear regression with the help of statistical package for the social science (SPSS) Version 20 software. Distributed questionnaires utilize ordinal scales. The results showed that the regression coefficient value of the Budget Participation variable of 0.229 with a calculated t value of 2.107 was greater than the table t value of 1.679 so that it could be stated that budget participation had a significant effect on managerial performance. The results of the study on the variable clarity of budget targets showed that the value of the regression coefficient of 1.322 with a calculated t value of 5.009 was greater than the table t value of 1.679 so that it can be stated that the clarity of budget targets has a significant effect on managerial performance at the Makassar City Office Joint Office